2016
DOI: 10.1590/1678-69712016/administracao.v17n5p110-137
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the New Franchise Creation Decision: The Relevance of Behavioral Reasons

Abstract: Este artigo pode ser copiado, distribuído, exibido, transmitido ou adaptado desde que citados, de forma clara e explícita, o nome da revista, a edição, o ano, e as páginas nas quais o artigo foi publicado originalmente, mas sem sugerir que a RAM endosse a reutilização do artigo. Esse termo de licenciamento deve ser explicitado para os casos de reutilização ou distribuição para terceiros. Não é permitido o uso para fins comerciais. In 2014, the Brazilian Franchising Association reported 2,492 active brands in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 35 publications
0
2
0
1
Order By: Relevance
“…These results seem to reflect that the behavior of franchises in Mexico is more intense in the use of franchised units as they acquire more experience and size coinciding with previous studies (Alon, 2001; Castrogiovanni et al, 2006a; Combs & Castrogiovanni, 1994). Additionally, it could be argued that the franchisers that adopt a greater franchising intensity pursue not only economic objectives, Aguiar, Pauli, Yu, and Nascimento (2016) found that there are motivational factors that drive franchisors to achieve status, as this status is a positive sign of professional and financial success of their concepts.…”
Section: Discussionmentioning
confidence: 99%
“…These results seem to reflect that the behavior of franchises in Mexico is more intense in the use of franchised units as they acquire more experience and size coinciding with previous studies (Alon, 2001; Castrogiovanni et al, 2006a; Combs & Castrogiovanni, 1994). Additionally, it could be argued that the franchisers that adopt a greater franchising intensity pursue not only economic objectives, Aguiar, Pauli, Yu, and Nascimento (2016) found that there are motivational factors that drive franchisors to achieve status, as this status is a positive sign of professional and financial success of their concepts.…”
Section: Discussionmentioning
confidence: 99%
“…There are several motivations underlying the decision for franchisors to expand through franchising. Extant literature identifies entrepreneurial characteristics (Evanschitzky, Caemmerer, & Backhaus, ), economic reasons (Aguiar, Pauli, Yu, & Nascimento, ; Madanoglu, Alon, & Shoham, ), saturation in the domestic market (Elango, ), acquisition of additional capital, economies of scale, competitive advantage, opportunism (Doherty, Chen, & Alexander, ), and risk reduction (Sun & Lee, ) as some of the motivating factors for franchising. The agency theory, resource scarcity theory, and risk‐reducing theory are some of the theoretical groundings that can explain motivations for franchisors to adopt a franchising strategy (Sun & Lee, ).…”
Section: Motivations For Franchisingmentioning
confidence: 99%
“…Partindo-se dos dados elencados acima, reforça-se um maior nível de concorrência agregada entre as franquias, de forma que as redes necessitam se diferenciar umas das outras e mostrar uma maior atratividade para conquistarem novos franqueados. Entre esses diferenciais, é necessário mostrar que as redes são rentáveis, que possuem um modelo de negócio sustentável do ponto de vista econômico, que estão bem posicionadas no mercado e que possuem uma reputação positiva perante o mercado (Brandt, 2007;Monge & Huerta, 2015;Aguiar, Pauli, Yu, & Nascimento, 2016).…”
Section: Introductionunclassified